Cerebroplacental Ratio (CPR) as predictor of perinatal outcome in induction of labour - Salleh, M Fairudzi Afzanizam; Ismail, Hamizah; Pasi, Hafizah; Ismail, Rozihan; Nusee, Zalina (2018)
Doppler velocimetry studies of the placenta and the fetal circulation provide important information regarding the fetal well-being. When apply in appropriate conditions it may provide an opportunity to improve the perinatal outcome. Objective : To assess the usefulness of cerebro-placental ratio (CPR) Doppler in predicting perinatal outcomes among women who were scheduled for induction of labor. Methodology: There were 203 antenatal women recruited for CPR Doppler studies at 37 week and above gestations. CPR less than 1 was taken as predictor of adverse perinatal outcomes. The adverse perinatal outcomes were evaluated by intrapartum cardiotocograph (CTG), mode of delivery, meconeium-stained liquor, arterial cord blood pH, Apgar score at 5 minutes and admission to neonatal intensive care unit (NICU). Result: Low CPR was significantly associated with abnormal intrapartum CTG (p<0.001), caesarean or operative deliveries for fetal compromised (p<0.001) and low arterial cord blood pH (p<0.001). Conclusion : CPR was a valuable investigation in predicting the perinatal outcomes prior to induction of labor.